2015
DOI: 10.1128/jb.02278-14
|View full text |Cite
|
Sign up to set email alerts
|

AterDDomain-Encoding Gene (SCO2368) Is Involved in Calcium Homeostasis and Participates in Calcium Regulation of a DosR-Like Regulon in Streptomyces coelicolor

Abstract: bAlthough Streptomyces coelicolor is not resistant to tellurite, it possesses several TerD domain-encoding (tdd) genes of unknown function. To elucidate the function of tdd8, the transcriptomes of S. coelicolor strain M145 and of a tdd8 deletion mutant derivative (the ⌬tdd8 strain) were compared. Several orthologs of Mycobacterium tuberculosis genes involved in dormancy survival were upregulated in the deletion mutant at the visual onset of prodiginine production. These genes are organized in a putative redox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Recently, it was shown that the DraRK TCS, which responds to high concentrations of nitrogen 113 , and the OsdRK TCS, which is oxygen6responsive, are similar in function to the system controlling dormancy in mycobacteria 112,120 , and are both required for Act production. Interestingly, in the absence of a functional DraRK system the production of…”
Section: Pathway Specific Regulation: Streptomycin and Actinorhodin Amentioning
confidence: 99%
“…Recently, it was shown that the DraRK TCS, which responds to high concentrations of nitrogen 113 , and the OsdRK TCS, which is oxygen6responsive, are similar in function to the system controlling dormancy in mycobacteria 112,120 , and are both required for Act production. Interestingly, in the absence of a functional DraRK system the production of…”
Section: Pathway Specific Regulation: Streptomycin and Actinorhodin Amentioning
confidence: 99%
“…These include a batch of 'universal stress response' proteins and ABC transporters and, notably, 14 of these translationally-induced genes are contained within a 50-gene segment of the 'redox stress response' cluster (SCO0162-SCO0212) close to one end of the chromosome 33,34 . These gene products are considered to play a critical role in stress adaptation because the genes are induced only at the level of translation, avoiding the requirement for additional transcription; this regulatory strategy ensures a near instantaneous response to the environmental stressor.…”
Section: Extensive Changes In 'Translation Efficiency' Occur During Hmentioning
confidence: 99%
“…Mycelia from the same bacterial cultures used in the polysome profiling experiments were treated with RNA Protect Bacteria Reagent and total RNA was extracted following a modified version of the method as described in 34 . In brief, the mycelia was harvest from four plates with a spatula and, after treatment with RNA protect Bacteria Reagent (Qiagen), was resuspended and lysed in 200 μ L Tris-EDTA plus Lysozyme (15mg/ml).…”
Section: Transcriptome Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The deletion of either RR gene was shown to enhance the production of actinorhodin, the blue-pigmented antibiotic of Streptomyces coelicolor . Although no biochemical evidence was provided, it was previously suggested that sensory kinase SCO0203 may be a direct orthologue of DosT, an SK from a well-studied TCS from the pathogenic obligate aerobe Mycobacterium tuberculosis ( 10 ).…”
Section: Introductionmentioning
confidence: 99%